1970
DOI: 10.1039/j19700003064
|View full text |Cite
|
Sign up to set email alerts
|

Metal–metal bonding in co-ordination complexes. Part IX. Crystal structure of trans-di-µ-carbonyl-dicarbonyldi-π-cyclopentadienyldi-iron (Fe–Fe), a redetermination

Abstract: The c rysta I st ru ct u re of the trans-isomer of d ip-car b o n y Id i c a r b o n y Id i -7 ~-c y cl o pe n t a d i e n y I d iiron has been redetermined by three-dimensional methods. The space group is P2Jc with a = 7.046(1), b = 12.453(2), c = 7.990(1) A, p = 108.44(1)", and Z = 2. The 904 reflections measured by counter diffractometry were used in the refinement by block-diagonal least-squares methods. With individual anisotropic thermal parameters and no allowance for hydrogen atom contributions, R = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…The Fe(2)-Fe(2 * ) distance is quite short and clearly indicative of an Fe-Fe bonding interaction. The Fe(2)-Fe(2 * ) distance of 2.545(1) Å and is very similar to the Fe-Fe distance in [CpFe(CO) 2 ] 2 , cis-isomer, 2.531(1) Å [10]; trans-isomer, 2.534(2) Å [11]. The S(2)-S(3) bond distance 2.0711 (14) Å is quite similar to the S-S bond distances observed in compounds 1 and 2.…”
Section: Cyclic Voltammetrymentioning
confidence: 59%
See 1 more Smart Citation
“…The Fe(2)-Fe(2 * ) distance is quite short and clearly indicative of an Fe-Fe bonding interaction. The Fe(2)-Fe(2 * ) distance of 2.545(1) Å and is very similar to the Fe-Fe distance in [CpFe(CO) 2 ] 2 , cis-isomer, 2.531(1) Å [10]; trans-isomer, 2.534(2) Å [11]. The S(2)-S(3) bond distance 2.0711 (14) Å is quite similar to the S-S bond distances observed in compounds 1 and 2.…”
Section: Cyclic Voltammetrymentioning
confidence: 59%
“…The known compound [CpFe(CO) 2 ] 2 can subsequently be eluted from the baseline in approx. 20% yield by using pure CH 2 Cl 2 elution solvent [10,11].…”
Section: Reaction Of [Cpfemn(co) 5 (L 3 -S 2 )] 2 (1) With Comentioning
confidence: 99%
“…The X-ray and neutron diffraction studies [7][8][9] showed that I has a centrosymmetric structure in the solid phase with two bridging and two terminal carbonyl groups (trans-bridged form). Low-temperature crystallization made possible isolation of the cis form [10].…”
Section: Experimental Datamentioning
confidence: 99%
“…The first low energy band of [Re 2 (CO) 10 ] was suggested to overlap with the intense near-UV band [37]. For [Co 2 (CO) 8 ] two low energy bands at about 430 and 410 nm were ascribed to dAEs * transitions in the non-bridged and bridged isomers, respectively, and two higher energy bands at about 350 and 280 nm were ascribed to sAEs * transitions in non-bridged and bridged isomers, respectively [39].…”
Section: Calculated Spectramentioning
confidence: 99%
“…The title compound is an intermediate in the synthesis of polymers with Fe Fe bonds in the backbone . The Fc Co--Fe bridge is slightly asymmetric compared with that in the parent trans-Fea(CO)a(CsHs)2 (Bryan & Greene, 1970), but other dimensions are not significantly affected. Intermolecular hydrogen bonds are also present in Mo2(CO)6(CsHaCH2CH2OH)2 (Tenhaeff, Tyler & Weakley, 1991).…”
mentioning
confidence: 90%